(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we are interested in proving a general fixed point theorem for multivalued mappings in fuzzy b−metric spaces. The results presented in this paper not only generalize the findings from [23], but also yield additional specific outcomes. We present an application to establish the existence of a solution to the integral equation, demonstrating the significance of our result.